Transgenerational Adaptation to Heavy Metal Salts in Arabidopsis - Reza Rahavi, Mohammad; Migicovsky, Zoe D.; Titov, Viktor; Kovalchuk, Igor (Frontiers in Plant Science, 2011)
Exposure to abiotic and biotic stress results in changes in plant physiology and triggers genomic instability. Recent reports suggest that the progeny of stressed plants also exhibit changes in genome stability, stress tolerance, and methylation. Here we analyzed whether exposure to Ni2+, Cd2+, and Cu2+ salts leads to transgenerational changes in homologous recombination frequency and stress tolerance. We found that the immediate progeny of stressed plants exhibited an increased rate of recombination. However, when the progeny of stressed plants was propagated without stress, recombination reverted to normal levels. Exposure of plants to heavy metals for five consecutive generations (S1–S5) resulted in recombination frequency being maintained at a high level. Skipping stress following two to three generations of propagation with 50 mM Ni2+ or Cd2+ did not decrease the recombination frequency, suggesting plant acclimation to upregulated recombination. Analysis of the progeny of plants exposed to Cu2+ and Ni2+ indicated higher stress tolerance to the heavy metal parental plants were exposed to. Tolerance was higher in plants propagated with stress for three to five generations, which resulted in longer roots than plants propagated on heavy metals for only one to two generations. Tolerance was also more prominent upon exposure to a higher concentration of salts. The progeny of stressed plants were also more tolerant to NaCl and methyl methane sulfonate.